Telicidad y alcance en las frases nominales - Romina Trebisacce (Quintú Quimün, 2018)
In this article we revise the configurational proposal to telicity that states that the interpretation of a telic event is associated with a particular syntactic projection (above VP in the syntactic structure) where the object raises (Kratzer, 2004; Thompson, 2006). This hypothesis is not compatible with some previous work that argues for a correlation between the syntactic position of NPs and their scope (Diesing, 1992; López, 2012) and for obligatory wide scope of NPs that move out of VP. The aim of this article is to present a calculation model of telicity that preserves the association between information on the telic event and its syntactic position. Furthermore, we claim that the object does not move. Concretely, we propose that the αP projection (López, 2012), which is obligatory, contains information on the telicity of the event. In semantic terms, α is a function with two possible denotations depending on the syntactic context. On the one hand, it can be an identity function, when it combines with bare plurals; on the other hand, it can be an identity function with the requirement of culmination, when combined with singular indefinites.